Synergistically Promoting Bone Regeneration by Icariin-Incorporated Porous Microcarriers and Decellularized Extracellular Matrix Derived From Bone Marrow Mesenchymal Stem Cells - Zhou, Mengyang; Guo, Min; Shi, Xincui; Ma, Jie; Wang, Shutao; Wu, Shuo; Yan, Weiqun; Wu, Feng; Zhang, Peibiao (Frontiers in Bioengineering and Biotechnology, 2022)
Multifunctionality has becoming essential for bone tissue engineering materials, such as drug release. In this study, icariin (ICA)-incorporated poly(glycolide-co-caprolactone) (PGCL) porous microcarriers were fabricated and then coated with decellularized extracellular matrix (dECM) which was derived from bone marrow mesenchymal stem cells (BMSC). The porous structure was generated due to the soluble gelatin within the microcarriers. The initial released ICA in microcarriers regulated osteogenic ECM production during ECM formation. The dECM could further synergistically enhance the migration and osteogenic differentiation of BMSCs together with ICA as indicated by the transwell migration assay, ALP and ARS staining, as well as gene and protein expression. Furthermore, in vivo results also showed that dECM and ICA exhibited excellent synergistic effects in repairing rat calvarial defects. These findings suggest that the porous microcarriers loaded with ICA and dECM coatings have great potential in the field of bone tissue engineering.